3D Model Search and Retrieval Using the Spherical Trace Transform. (23rd October 2006) - Zarpalas Zarpalas, Dimitrios Dimitrios; Daras Daras, Petros Petros; Axenopoulos Axenopoulos, Apostolos Apostolos; Tzovaras Tzovaras, Dimitrios Dimitrios; Strintzis Strintzis, Michael G. Michael G.
Abstract : This paper presents a novel methodology for content-based search and retrieval of 3D objects. After proper positioning of the 3D objects using translation and scaling, a set of functionals is applied to the 3D model producing a new domain of concentric spheres. In this new domain, a new set of functionals is applied, resulting in a descriptor vector which is completely rotation invariant and thus suitable for 3D model matching. Further, weights are assigned to each descriptor, so as to significantly improve the retrieval results. Experiments on two different databases of 3D objects are performed so as to evaluate the proposed method in comparison with those most commonly cited in the literature. The experimental results show that the proposed method is superior in terms of precision versus recall and can be used for 3D model search and retrieval in a highly efficient manner.